Patterns of missing data in the use of the endometriosis symptom diary - Christian Seitz; Vivian Lanius; Susanne Lippert; Christoph Gerlinger; Claudia Haberland; Frank Oehmke; Hans-Rudolf Tinneberg (BMC, 2018)
Abstract Background Endometriosis is a common, chronic condition in women of reproductive age that is characterized by the presence of functional endometriotic lesions outside the uterus. The Endometriosis Symptom Diary (ESD) is an electronic patient-reported outcome (ePRO) instrument that assesses women's experience of endometriosis symptoms, with pain scored using a 0-10 numeric rating scale. This study investigated patterns of data missing from the ESD in the VALEPRO study. Methods Post hoc analyses of missing data were conducted. Results Of 272 participants using the ESD, 26.5% had no missing diary entries, 46.7% had > 0-5% of entries missing, 13.2% had > 5-10% of entries missing and 13.6% had > 10% of entries missing over the entire study period. The duration of missing episodes (defined as ≥1 consecutive days with missing diary entries) was generally short; most (81.4%) were 1 day. The difference in mean worst pain scores between missing and complete episodes per participant was − 0.1, suggesting that missing episodes were not related to severity of pain. Entries were significantly more likely to be missing on Fridays (18.5%) and Saturdays (22.9%) compared with other days of the week (p < 0.0001). Participants in the USA had significantly more long missing episodes than those in Germany (proportions of missing episodes longer than 1 day, 22.6 and 10.5%, respectively; p < 0.0001). The proportions of women with ≥1 missing entry were 50.0, 70.2 and 79.8% for women with elementary education, secondary education, and a college or university education, respectively. The proportions of women with ≥1 missing entry were similar for those with and without children (72.2 and 74.3%, respectively). Conclusions Most participants were highly compliant with entering data in the ESD and the amount of missing data was low. Entries were significantly more likely to be missing on Fridays and Saturdays compared with other days of the week, and participants in the USA had significantly more long missing episodes than participants in Germany. Trial registration Clinicaltrials.gov, NCT01643122, registered 4 July 2012.